2019
DOI: 10.1098/rsos.181702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mis-alignment between dispersal traits and landscape structure on dispersal success in fragmented landscapes

Abstract: Dispersal is fundamental to population dynamics and hence extinction risk. The dispersal success of animals depends on the biophysical structure of their environments and their biological traits; however, comparatively little is known about how evolutionary trade-offs among suites of biological traits affect dispersal potential. We developed a spatially explicit agent-based simulation model to evaluate the influence of trade-offs among a suite of biological traits on the dispersal success of vagile animals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 102 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…TRA provided habitat for common species that favor open secondary forest (Rutt et al., 2019), forest edge with cattle pasture, and primary forest due to shared vegetation structure and composition qualities relative to PRES and DIS. The common species of PRES and DIS with high mobility find resources at sections of TRA that are adjacent to PRES and DIS (Atkins et al., 2019). However, TRA did not have higher overall species diversity relative to PRES and DIS.…”
Section: Discussionmentioning
confidence: 99%
“…TRA provided habitat for common species that favor open secondary forest (Rutt et al., 2019), forest edge with cattle pasture, and primary forest due to shared vegetation structure and composition qualities relative to PRES and DIS. The common species of PRES and DIS with high mobility find resources at sections of TRA that are adjacent to PRES and DIS (Atkins et al., 2019). However, TRA did not have higher overall species diversity relative to PRES and DIS.…”
Section: Discussionmentioning
confidence: 99%
“…, Atkins et al. ). Overall, these studies have reported reduced dispersal propensity or capacity in fragmented landscapes, which is usually attributed to prohibitive costs during the transition phase across the matrix (Cheptou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Different life history traits may therefore be related to successful dispersal in both processes, and mixing both continental and oceanic barriers can obscure life history–dispersal relationships. Biogeographic dispersal may hence be context dependent (depending on the type of barrier and possibly their characteristics, that is, environmental harshness and degree of landscape fragmentation, as has been shown for active, short-distance dispersal previously 29 , 30 ). Future work should therefore aim to consider different types of barriers separately (which is not possible in the present study due to computational constraints; Methods and Supplementary Information Section 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in some clades, large species with an extreme life history strategy were better dispersers (for example, Chamaeleonidae and Corvidae), and in other clades species with fast life history strategies but small body sizes were better dispersers (for example, Cricetidae and Dasyuridae). Multiple traits may therefore interact in their influence on biogeographic dispersal 33 , and this influence may be mediated by the environment and/or biotic interactions 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%